2013
DOI: 10.4149/neo_2013_057
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Hoxc6 expression is associated with poor survival in gastric cancer patients

Abstract: Human Hox genes (Homeobox) have crucial roles in development and differentiation, regulating numerous processes including apoptosis, receptor signalling, differentiation, motility and angiogenesis. Aberrant expression of Hoxc6 gene has been reported in several tumor tissues and cancer cell lines. The prognostic significance of Hoxc6 in gastric cancer remains largely unknown.This study was aimed to investigate the clinical significance of Hoxc6 in gastric cancer.Total RNA of paired tissue samples (n=25) and a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 19 publications
2
37
0
1
Order By: Relevance
“…Transcription factor HOXC6 is a member of a highly conserved homeobox family of transcription factors that play an important role in proliferation as well as in morphogenesis and metastasis and regulates genes with both oncogenic and tumor suppressor activities and may contribute to the progression of gastric carcinogenesis [30]. Recently was shown that knockdown of endothelial PAS domain protein 1 (EPAS1), which also known as hypoxiainducible transcription factor-2alpha (HIF-2α), as well as HIF-1α decreased cell proliferation under normoxic as well as hypoxic conditions in pulmonary vascular endothelial cells and that EPAS1/HIF-2α and SOX9 regulate TUBB3 gene expression and affect ovarian cancer aggressiveness [31]. Moreover, the expression of EPAS1 gene was significantly correlated with tumor size, invasion, and necrosis as well as with VEGF gene expression, which supported the correlation of EPAS1 up-regulation with tumor angiogenesis [32].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor HOXC6 is a member of a highly conserved homeobox family of transcription factors that play an important role in proliferation as well as in morphogenesis and metastasis and regulates genes with both oncogenic and tumor suppressor activities and may contribute to the progression of gastric carcinogenesis [30]. Recently was shown that knockdown of endothelial PAS domain protein 1 (EPAS1), which also known as hypoxiainducible transcription factor-2alpha (HIF-2α), as well as HIF-1α decreased cell proliferation under normoxic as well as hypoxic conditions in pulmonary vascular endothelial cells and that EPAS1/HIF-2α and SOX9 regulate TUBB3 gene expression and affect ovarian cancer aggressiveness [31]. Moreover, the expression of EPAS1 gene was significantly correlated with tumor size, invasion, and necrosis as well as with VEGF gene expression, which supported the correlation of EPAS1 up-regulation with tumor angiogenesis [32].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of fz2, hoxc6a, tcf3b and wnt5b was much higher in whsc1 −/− zebrafishes than that in wild-type ones (Figure 7). Coincidently, abnormal expression of hoxc6a [23], [24], [25] and wnt5b [26], [27], [28] have been shown to be related with cancers.
Figure 7 whsc1 −/− zebrafish exhibited disordered expression of genes involved in swim bladder formation. mRNA levels of indicated genes were normalized to b-actin.
…”
Section: Resultsmentioning
confidence: 95%
“…ACTB (β-actin) from Santa Cruz Biotechnology was used as control of analyzed protein quantity in extracts of glioma cells. Western blot analysis was performed as described previously [34].…”
Section: Methodsmentioning
confidence: 99%
“…Transcription factor HOXC6 is a member of a highly conserved homeobox family of transcription factors that play an important role in proliferation as well as in morphogenesis and metastasis and regulate genes with both oncogenic and tumor suppressor activities and may contribute to the progression of gastric carcinogenesis [27,33,34]. Recently it was shown that the forkhead box transcription factor FOXF1 is a target of the TP53 family and its ectopic expression inhibits cancer cell invasion and migration, whereas the inactivation of FOXF1 stimulated both these processes [28,35].…”
Section: Hypoxia As Well As the Endoplasmic Reticulum Stress Are Impomentioning
confidence: 99%
See 1 more Smart Citation